SOIL TEMPERATURE CONTROL FOR GROWING OF HIGH-VALUE TEMPERATE CROPS ON TROPICAL LOWLAND - Rasaq Adekunle Olabomi; Bakar Jaafar; Md Nor Musa; Shamsul Sarip (Malaysian Journal of Sustainable Agriculture, 2022)
Low soil temperature (14℃–20℃) favours growing of high-value temperate crops that are known to have higher return per hectare of land than other widely cultivated crops, thereby presenting increased income to farmer. However, due to high soil cooling load, growing these crops on tropical lowland area is a challenge except through greenhouse farming or on few cool higher altitudes with resemblance of temperate climate. Greenhouse farming involves cooling the entire volume of planting zone and is energy intensive, while few cool highlands are not sufficient to achieve food security in this direction. This study aims at application of chilled water for direct cooling of soil, to create favorable soil conditions for optimal performance of planted temperate crops. However, soil cooling using vapour compression refrigeration system may not be economically viable. Solar thermal chilled water production system is presented in this study to supply the cooling. The system consists of absorption refrigeration system and dimensioned size of soil bed with chilled water pipe network. The study includes modeling of soil cooling load to determine the refrigeration power required to overcome such load. The modeled system matched well with the experiment; having standard deviation of 1.75 and percentage error of 12.24%. Parametric analysis of the soil cooling showed that temperatures of cooled soil were significantly affected by chilled water flow rates. The regression equation developed from the Analysis of Variance (ANOVA) is suitable for predicting cooled soil temperature. The cooling process is technically feasible, with potential for greenhouse gas emission reduction.